Seed technology and production of improved maize varieties from INIFAP without PRONASE. - Espinosa-Calderón, Alejandro; Sierra-Macías, Mauro; Gómez-Montiel, Noel (Agronomía Mesoamericana, 2003)
The National Institute of Research on Forestry, Agriculture, and Livestock (INIFAP) of Mexico, with other preceding institutions have released 221 hybrids and developed varieties during 62 years. This time INIFAP has worked in maize plant breeding. The genotypes had specific adaptation to different environmental conditions. The materials were maize double-crossed and Open Pollinated Varieties (OPV). Both varieties were recommended to cover the largest possible areas. The National Seed Producing Enterprise (Productora Nacional de Semillas, PRONASE); was founded in 1961. The Seed Law support PRONASE. Under the new seed law, passed in 1961, several regulatory entities were established to control crop research and seed certification, production and marketing. Officially, all research was controlled by the Ministry of Agriculture. The creation of PRONASE, with its mandate to produce and distribute commercial seed of all varieties developed by INIFAP, created a quasi-monopoly in the seed industry, which limited and delayed the private sector’s participation in research and seed production. Eventhough, privatisation substantially changed the public and private sector participation in maize seed production and sale. The Mexican seed industries are relatively limited by the participation of NGOs and cooperatives in maize seed production and marketing. Cooperatives and NGOs produce and market seed, especially of improved OPVs. Public organisations have dismissed almost completely from seed production and marketing. Multinational and several national companies dominate the industry by supporting strong breeding programs. However, the use of certified seed is small (26% to 33%). The INIFAP has released improved and new varieties (30), all of them with good agronomic characteristics for the different regions of Mexico. INIFAP has Seed Technology and Seed production. It is necessary to improve some strategies to supply seed. The farmers can establish small local seed enterprises.